The Impact of the Covid‐19 Global Health Pandemic in Early Childhood Education Within Four Countries - McNair, Lynn (2022)
The recent Covid‐19 global health pandemic has negatively affected the political and economic development of communities around the world. This article shares the lessons from our multi‐country project Safe, Inclusive Participative Pedagogy: Improving Early Childhood Education in Fragile Contexts (UKRI GCRF) on how children in communities in Brazil, Eswatini, South Africa, and Scotland have experienced the effects of the pandemic. This article benefits from having co‐authors from various countries, bringing their own located knowledge to considerations of children’s rights and early childhood education in the wake of the pandemic. The authors discuss different perspectives on children’s human rights within historical, social, and cultural contexts and, by doing so, will discuss how the global pandemic has placed a spotlight on the previous inequalities within early years education and how the disparity of those with capital (economic and social) have led to an even greater disproportion of children needing health and educational support.